Digital Verification of Optically Variable Ink Feature on Identity Cards - Lucia Piatriková; Peter Tarábek; Ivan Cimrak (Proceedings of the XXth Conference of Open Innovations Association FRUCT, 2023)
Digital identity verification is a new trend that allows clients to access services and products remotely, simplifies the interaction between client and institution, and saves their expenses. Digital verification suffers many security risks. The system must be able to reveal counterfeit identity cards. We propose a procedure to verify ID cards based on an analysis of the Optically Variable Ink (OVI) security feature. OVI is a type of ink whose colour varies with rotation or changes in observer or light source position. The proposed method can detect an ID card and an OVI security feature on video frames. OVI visual characteristics are analysed, and we provide methods for their visual verification. We make several recommendations and suggestions for solving various partial problems related to visual OVI verification. Proposed methods can reveal counterfeit ID card in a video by analysing the OVI security feature with an accuracy of 82.82% but with some limitations.